PENGARUH RETURN ON EQUITY, RECEIVABLE TURN OVER DAN DEBT EQUITY RATIO TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019–2023) - Ridwan, Riffatka; Priharta, Andry; Zulkarnain, Iskandar (Taksasila Edukasi Insani, 2025)
This study aims to analyze the effect of Return on Equity (ROE), Receivable Turn Over (RTO), and Debt to Equity Ratio (DER) on stock prices in insurance companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. A quantitative approach was applied using multiple linear regression analysis with EViews 12 software. The study utilized secondary data from the annual financial reports of 11 insurance companies selected through purposive sampling. The findings indicate that partially, ROE, RTO, and DER do not have a significant effect on stock prices, as indicated by p-values above 0.05. Simultaneously, the three variables also have no significant effect on stock prices, with an F-statistic value of 0.7591 and a probability of 0.6657. The coefficient of determination (R²) is 0.6949, indicating that 69.49% of the variation in stock prices is explained by the model; however, the negative adjusted R² (-0.2205) suggests the model is inefficient. These results imply that financial variables such as ROE, RTO, and DER are not sufficient to significantly explain stock price movements in the insurance sector, and future research is recommended to incorporate other variables.Keywords : Debt to Equity Ratio, Insurance Companies, Multiple Linear Regression, Receivable Turn Over, Return on Equity